Human antibodies eluted from ligand-free Sepharose capable of binding bacterial polysaccharides and sulfated glycans. (February 2019) - Dobrochaeva, K.L.; Khasbiullina, N.R.; Shilova, N.V.; Obukhova, P.S.; Knirel, Yu.A.; Nokel, A.Yu.; Bovin, N.V.
Highlights: Human blood contains antibodies capable of binding to glycan-ligand-free Sepharose. 'Anti-Sepharose' antibodies bind bacterial polysaccharides and sulfated glycans. β-d -Gal seems to be a mimotope for α-l -Rha containing polysaccharides. Part of antibodies recognize spatial rather than linear epitopes in polysaccharides. Abstract: Sepharose matrix without immobilized ligands binds antibodies from human blood serum or immunoglobulin preparations. The eluted antibodies bind bacterial polysaccharides having no structural similarity to agarose (Sepharose is a cross-linked polysaccharide agarose) with a high affinity. It is concluded that the identified antibodies are capable of recognizing spatial rather than linear epitopes of bacterial polysaccharides. This side activity of Sepharose matrix should be taken into account in isolating target antibodies and other proteins from human blood.